Protein unfolding in crowded milieu: what crowding can do to a protein undergoing unfolding?. Issue 10 (2nd October 2016) - Stepanenko, Olga V.; Povarova, Olga I.; Sulatskaya, Anna I.; Ferreira, Luisa A.; Zaslavsky, Boris Y.; Kuznetsova, Irina M.; Turoverov, Konstantin K.; Uversky, Vladimir N.
Abstract : The natural environment of a protein inside a cell is characterized by the almost complete lack of unoccupied space, limited amount of free water, and the tightly packed crowd of various biological macromolecules, such as proteins, nucleic acids, polysaccharides, and complexes thereof. This extremely crowded natural milieu is poorly mimicked by slightly salted aqueous solutions containing low concentrations of a protein of interest. The accepted practice is to model crowded environments by adding high concentrations of various polymers that serve as model "crowding agents" to the solution of a protein of interest. Although studies performed under these model conditions revealed that macromolecular crowding might have noticeable influence on various aspects related to the protein structure, function, folding, conformational stability, and aggregation propensity, the complete picture describing conformational behavior of a protein under these conditions is missing as of yet. Furthermore, there is an accepted belief that the conformational stability of globular proteins increases in the presence crowding agents due to the excluded volume effects. The goal of this study was to conduct a systematic analysis of the effect of high concentrations of PEG-8000 and Dextran-70 on the unfolding behavior of eleven globular proteins belonging to different structural classes.